MENGENAL PENDIDIKAN KEIMANAN DALAM AL-QURAN - Hoktaviandri, Hoktaviandri (Institut Agama Islam Negeri (IAIN) Metro, 2017)
Man was created by Allah SWT as a peadagogical creature in the sense of having the potential to be educated and educated. In principle the goal of man is created is to worship him. Anything done just wishes Allah SWT. For worship that is done in accordance with his expected then the deed should be based on faith. The potential of faith has existed from the time humans were born. Therefore, faith needs to be continually nurtured through education.